Dilemmas of Federalism and the Dynamics of the Australian Case - Fenna, Alan; Hollander, R. (Blackwell Publishing Asia P/L, 2013)
This paper provides a synoptic account of the distinguishing features and broad tendencies of federal systems in general and the main characteristics and challenges of Australian federalism in particular. In doing so, it canvasses questions of purpose and rationale, constitutional design and evolution as well as fiscal federalism and intergovernmental relations. It highlights the obsolescence of the traditional division of powers around which Australian federalism was originally organised; the degree to which the system has become centralised; and the search for a new basis on which the two levels of government can most effectively and efficiently work together in today's world of concurrent responsibility.